A review of prospective registration of trials published in nursing science journals in 2017. (30th July 2019) - Gray, Richard; Gray, George; Brown, Ellie
Abstract: Aim: To determine the proportion of trials published in nursing science journals in 2017 that were prospectively registered. Design: A review of randomized controlled trials published in a Journal Citation Report nursing science journal in 2017. Data source: Table of contents of included journals. Review methods: Randomized controlled trials were identified by manually reviewing the title of all papers published in included journals. Included trials were classified as: (a) Prospectively registered; (b) Retrospectively registered; (c) Registered but registration not reported in the manuscript; (d) Indeterminate registration; and (e) Not registered. Additionally, we recorded if the trial registration number was reported in the manuscript abstract. Results: Of 151 randomized controlled trials published in nursing science journals in 2017, 17 (11%) were prospectively registered. Thirty‐six (24%) trials were retrospectively and 93 (62%) not registered. We could not determine the registration status of five (3%) trials. The registration number was included in the abstract of two prospectively and eight retrospectively registered studies. Compared with the rest of the world, trial registration rates were significantly lower in Asian countries. Conclusion: Two included trials were prospectively registered and reported a registration number in the abstract. Compared with other disciplines, rates of prospective trial registration are low. Nurse trialists must ensure that they prospectively register all trials. Impact: We intended to replicate this review in subsequent years with a view to reporting improvements in prospective registration rates over time. Abstract : 目的: 确定对2017年护理学期刊所载试验进行前瞻性登记的比例。 设计: 评价2017年发表在期刊引文报告"护理学杂志"上的随机对照试验。 资料来源: 所纳入期刊的目录。 综述方法: 通过人工检查在所纳入期刊上发表的所有论文的标题, 确定随机对照试验。所纳入的试验分为:(a)前瞻性登记;(b)追溯性登记;(c)已登记但未在手稿中汇报登记情况;(d)未确定登记;(e)未登记。此外, 我们还记录了是否在手稿摘要中汇报试验登记号的情况。 结果: 2017年在护理学期刊上发表的151项随机对照试验中, 17项(11%)属于前瞻性登记。36项(24%)属于追溯性登记, 93项(62%)属于未登记。我们无法确定五项(3%)试验的登记情况。在两项前瞻性和八项追溯性登记研究的摘要中, 包含有登记号。与世界其他地区相比, 亚洲国家的试验登记率明显较低。 结论: 两项被纳入试验属于前瞻性登记, 并且, 在摘要中汇报了登记号。与其他学科相比, 前瞻性登记率较低。护理试验人员必须确保对所有试验进行前瞻性登记。 影响: 我们打算在今后几年重复开展这一评价, 以便汇报前瞻性登记率是否会随时间的推移而提高。